Comparative study of immune responses against Clostridium perfringens beta and epsilon toxoids in domestic and laboratory animals using neutralization test - HUQUE, A K M; RAHMAN, M S; LEE, J H (The Indian Journal of Animal Sciences, 2014)
The immune responses against the Clostridium peffringens beta and epsilon toxoids were investigated comparativelyin domestic and laboratory animals using the neutralization test. Apparently healthy 12 animals each of cattle, butfalos,sheep, goats, rabbits and guinea pigs were subcutaneously inoculated with the beta and epsilon toxoids. The blood wascollected at days 0, 14,21 for sera, and the neutralization tests were performed with the sera. Single dose with the beta andepsilon toxoids induced the immune responses in the animals on days 14 and 21 post inoculation, and there were noadverse reactions after the injection in any of the animals. Statistically significant (P